Meningkatkan Keaktifan Belajar Dan Bernalar Kritis Peserta Didik Pada Pembelajaran PAK Melalui Metode Discovery Learning - Misaya Misaya (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Misaya, Improving Students' Active Learning and Critical Reasoning in PAK Learning Through the Discovery Learning Method. Accompanied by Jelahu Timotius and Wahyuningtiyas as Tutor. The purpose of this Classroom Action Research is to find out and measure whether or not the activeness of learning and Critical Reasoning of fifth grade students at SD Negeri 008 Jempang, West Kutai Regency, East Kalimantan Province has increased using the Discovery Learning Method. The research subjects were 8 students in class V SD Negeri 008 Jempang, consisting of 6 boys and 2 girls. The object of research is the active learning and critical reasoning of students in Catholic Religion and Ethics lessons on the material